Use of Thoracic Trauma Severity Score (TTSS) Components and Systems in Predicting Mortality in Thoracic Trauma - Reynaldy C. Moksidy; Adrian Tangkilisan; Wega Sukanto (International Journal of Health and Pharmaceutical (IJHP), 2026)
Thoracic trauma contributes significantly to global mortality, necessitating early risk stratification to guide management. The Thoracic Trauma Severity Score (TTSS) integrates anatomical and physiological parameters to predict outcomes, but validation data from Southeast Asian populations remain limited. This retrospective cohort study included 77 thoracic trauma patients admitted to Prof. Dr. R.D. Kandou General Hospital, Manado, between 2021–2023. TTSS was calculated based on age, PaO₂/FiO₂ ratio, rib fracture count, pulmonary contusion, and pleural involvement. The primary outcome was in-hospital mortality. Statistical analyses included bivariate comparisons, Kaplan–Meier survival analysis, and receiver operating characteristic (ROC) curve analysis. Overall mortality was 29.9%. Non-survivors had significantly higher TTSS values than survivors (median 5 vs. 2.5, p < 0.001). Patients requiring ICU admission also demonstrated higher TTSS (median 6 vs. 3, p = 0.002). Pulmonary contusion (p = 0.021), PaO₂/FiO₂ ≤400 (p = 0.018), and age >30 years (p = 0.011) were significantly associated with mortality. ROC analysis showed good discriminatory ability for mortality (AUC ≈ 0.80, sensitivity 91%, specificity 50%). TTSS is a practical and effective tool for early mortality risk stratification in thoracic trauma patients, with good predictive performance. Its application in resource-limited settings may facilitate timely triage and escalation of care.